Post-Suburban Europe - Phelps, Nicholas A. author. aut Link
XIII, 233 p.
Keywords: The term 'edge city' describes the rapid growth of urban centres at the edge of established cities. Widely discussed in the US, very little has been written about European edge cities. This book gives a comparative analysis of examples in Greece, Spain, Paris, Finland and the UK, with a theoretical analysis of edge cities and post-suburban Europe.